Respiratory syncytial virus knowledge, attitudes, and perceptions among adults in the United States - Elizabeth M. La; Su Bunniran; Diana Garbinsky; Maria Reynolds; Phil Schwab; Sara Poston; Lauriane Harrington (Taylor & Francis Group, 2024)
ABSTRACTRespiratory syncytial virus (RSV) is associated with considerable morbidity and mortality among older adults (aged ≥60 years) and adults with certain chronic conditions in the United States (US). Despite this burden, no previous studies have assessed the knowledge, attitudes, and perceptions (KAP) of RSV among these populations. This study evaluates RSV-related KAP among US adults at increased risk of severe RSV infection. A cross-sectional, web-based survey was administered from May to June 2022 to better understand respiratory infection- and RSV-related KAP among US adults who are at risk of severe RSV infection. The survey included ≥200 adults in each of 4 subgroups: adults aged 60-89 years, and adults aged 18-59 years with ≥1 chronic cardiovascular condition, chronic pulmonary condition, or diabetes mellitus. Survey responses were analyzed descriptively overall and by subgroup, with exploratory logistic regression modeling used to evaluate characteristics associated with RSV awareness and concern. Among the 827 survey respondents, only 43.3% had ever heard of RSV (n = 358/827). The study identified key knowledge gaps (e.g. bacterial vs. viral nature of respiratory infections, RSV seasonality, common RSV symptoms, extent to which RSV causes respiratory infections in specific patient populations). Although 33.7% of RSV-aware adults (n = 120/356) reported being worried/very worried about RSV, 67.3% (n = 241/358) rarely consider RSV as a potential cause of their cold/flu-like symptoms. Results from this study highlight important knowledge gaps related to RSV, perceived risk, and severity of RSV. Findings can be used to support the development of tailored education efforts to support RSV prevention.